Pengaruh Kualitas Sistem Mobile Banking terhadap Laba Bersih dengan Penggunaan Sebagai Variabel Intervening - Taufan Adi Kurniawan; Dewi Kusuma Wardani; Ely Jupita Lestari (Universitas Muhammadiyah Metro, 2019)
The main objective of this study is to determine whether the quality of the system can affect the net benefits of using mobile banking both directly and through the variable of mobile banking usage. The type of data used is primary data. The data is taken from distributed questionnaire to BRI bank customers in Yogyakarta using mobile banking services. The sampling method used is convenience sampling. Data were analyzed using Partial Least Squares (PLS) available in SmartPLS 3.0 software application. the results of this study indicate that the quality of the system has a positive effect on usage. System benefits have a direct positive effect on net benefits. Usage is not an intervening variable in the relationship of system quality to net benefits.